DISCOURSE ANALYSIS OF LANGUAGE STYLE IN THE NOVEL CHAIRUL HARUN'S LEGACY - Rinaldi, Rio; Yulisna, Risa (ppjbsip, 2021)
This study aims to analyze the discourse with a focus on comparative language style and satire. This type of research is qualitative with descriptive method. The data source of this research is the novel Heritage by Chairul Harun. The data of this research are in the form of words that can be formulated as comparative figure of speech and satire based on the speech of the narrator and the characters. The data collection techniques in this study were: (1) reading the novel Heritage by Chairul Harun, (2) describing the data, and (3) recording the data that will be used as research material into a table. The data analysis technique is carried out by: (1) grouping the data into an analysis table, (2) determining the figure of speech contained in the speech of the character or the narrator's speech, (3) describing the results of the analysis, and (4) interpreting the results of the analysis by looking at the trend of using figure of speech. , and (5) conclude the results of the overall data analysis. Based on the data analysis and discussion, the results showed that the authors used comparative and satire figure of speech including personification, metonymy, allusion, metaphor, synecdoche, eponym, epithet, and simile. The dominant figure of speech in the novel Heritage by Chairul Harun is metaphorical figure of speech. Meanwhile, the satire figures found were satire, sarcasm, cynicism, innuendo, irony and antifrasis. The satire in the novel Heritage by Chairul Harun is dominantly cynical.